Arqueologia brasileira em 1968: um relatório preliminar sobre o Programa Nacional de Pesquisas Arqueológicas. - Brochado, José Proenza (Museu Paraense Emílio Goeldi, 2011)
Although Brazil includes a variety of a landscaps and climates, two large general divisions can be recognized: the Amazon basin and the Coastal Strip. These bioclimatic regions have independent prehistories, impling the existence of a strong natural barrier betwenn them. Along the Coastal Strip, the Preceramic Period lasted until about A.D. 500 except for an enclave on the Bahia coast. The earliest lithic complexes from the interior appear to lack stone projectiles points, but crude types occur in contemporary sambaquis. Otherwise, gros typology reveals little change in artifact types.